2020
DOI: 10.1002/app.49667
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of cinnamaldehyde microcapsule wall materials by experimental and quantitative methods

Abstract: Microencapsulation is a widely‐investigated technique used for the unstable material preservation since the wall materials prevent the core materials from loss and deterioration. To improve the stability of cinnamaldehyde (CAL), different microcapsule wall systems are fabricated by spray‐drying, and then characterized by experimental methods to determine the most suitable wall materials. Surface morphology, encapsulation efficiency, effective loading capacity, as well as moisture absorption property are evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…21,75,76 Li et al prepared a three-matrix system of methyl cellulose/carboxymethyl chitosan/sodium alginate using a spray drying method to encapsulate CA with a 50% encapsulation rate and a 4% loading capacity. 77 Physicochemical and biological studies showed that CA-loaded microcapsules exhibited enhanced resistance to oxidation, hydrolysis, and thermal decomposition, with prolonged storage and improved bioavailability. Xiao et al claimed that the encapsulation of CA using β-cyclodextrin significantly elevated the plasma CA concentration while reducing the levels of its metabolites in male C57/BL6 mice.…”
Section: Novel Delivery Systems For Cinnamaldehydementioning
confidence: 99%
“…21,75,76 Li et al prepared a three-matrix system of methyl cellulose/carboxymethyl chitosan/sodium alginate using a spray drying method to encapsulate CA with a 50% encapsulation rate and a 4% loading capacity. 77 Physicochemical and biological studies showed that CA-loaded microcapsules exhibited enhanced resistance to oxidation, hydrolysis, and thermal decomposition, with prolonged storage and improved bioavailability. Xiao et al claimed that the encapsulation of CA using β-cyclodextrin significantly elevated the plasma CA concentration while reducing the levels of its metabolites in male C57/BL6 mice.…”
Section: Novel Delivery Systems For Cinnamaldehydementioning
confidence: 99%